The Effect of Media Construction Through Labeling on the Perceived Risk of Victimization by the Ngruki Muslim Community Regarding Terrorism - Ireka, Radhistya (ADDIN, 2024)
The problem in this paper is that media construction can lead to the risk of victimization through the labeling given to the Ngruki community. The argument in this paper is that it is the media that reports on them so that a label is created that puts victimization at risk. How does the influence of media construction on the victimization risk through labeling that the Ngruki people feel? This paper aims to determine the effect of media construction on the risk of victimization through labels perceived by the Ngruki community. This paper uses a quantitative approach. Collection using survey techniques given to N: 133 respondents by random sampling. The analysis in this study uses the Partial Least Square Structural Equation Modeling (PLS-SEM) approach. The results show that media construction significantly affects labeling, and labeling significantly impacts the risk of victimization. While media construction significantly influences the risk of victimization through labeling. In conclusion, this paper shows that the media which constructs the Ngruki society with terrorism is biased and generalizes them. Ultimately, they feel the risk of victimization due to the label they receive.